Molecular identification of bacteriocins produced by Lactococcus lactis dairy strains and their technological and genotypic characterization. (May 2015) - Pisano, Maria Barbara; Fadda, Maria Elisabetta; Melis, Roberta; Ciusa, Maria Laura; Viale, Silvia; Deplano, Maura; Cosentino, Sofia
Abstract: In this study, the bacteriocins produced by ten Lactococcus lactis subsp. lactis strains, previously isolated from raw milk and traditional Sardinian cheeses, were identified by targeting and sequencing the bacteriocin encoding genes. The inhibitory activity against different food borne and spoilage bacteria, and the technological and genotypic characteristics of the bacteriocinogenic L. lactis strains were also analysed. The presence of the nisin structural gene was confirmed for all L. lactis strains. Three strains were shown to harbour the Lactococcins B structural gene. The sequences of PCR products for the nisin gene from the ten bacteriocinogenic strains were compared with that of L. lactis strain ATCC 11454 (nisin A producer strain). Differences were observed in strain 6LS5 indicating its ability to produce the nisin Z variant. Five strains presented a wider inhibitory spectrum resulting in activity towards Pseudomonas aeruginosa and all the Bacillus, Listeria, Staphylococcus and Clostridium strains tested. High β-galactosidase and moderate aminopeptidase activities, that promote the desirable flavours in cheese, were detected in the majority of the strains. Rep-PCR with primer (GTG)5 revealed high diversity among the strains and allowed discrimination at both interspecific and intraspecific level. The autochthonous bacteriocinogenic isolates from Sardinian dairy products described in this work may potentially find application as starter, co-starter or protective adjunct cultures in the manufacturing of cheeses. Highlights: Molecular identification of bacteriocins produced by ten Lactococcus lactis dairy strains. PCR gave positive amplifications for Nisin structural and Lactococcin B genes. A broader inhibition spectrum was observed in five L. lactis strains. Rep-PCR subtyping was used for genetic diversity analysis. These results contribute to enhance the number of technologically interesting LAB cultures.